Development of Automatic Watering System Using Arduino and Android Base for Southern Sissoo - Mohd Alim, Muhammad Hazim; Ibrahim, Noraini (Applied Information Technology And Computer Science, 2022)
Automatic Watering System is a mobile application watering schedule management system specifically develop to assist the watering session of crop for Southern Sissoo. Currently at the company, they lack manpower and hiring new worker is not an option as it will not benefit the company in the matter of long-term cost-effective. The main goal of this system development is to improve the quality of work at Southern Sissoo business particularly because they are still using the traditional physical watering method that has many flaws compared to today’s technique. Using Arduino and Android application, this system will increase in efficiency compared to the current physical method. With the proposed system, user can create custom watering session remotely from the farm and check the data of current and past temperature, humidity, light intensity and etc. The system will make the process of watering session and technique at the company improved and resource efficient.